The comprehension of idiomatic expressions in schizophrenic patients - Schettino, Antonio; Lauro, Leonor Romero; Crippa, Franca; Anselmetti, Simona; Cavallaro, Roberto; Papagno, Costanza (Neuropsychologia, 2010)
Recent fMRI and TMS studies on idiom comprehension have shown that the prefrontal cortex is involved in idiom processing. Since schizophrenic patients exhibit prefrontal structural changes and dysexecutive behavioural deficits, we hypothesised an impairment in idiom comprehension, correlating with performance on executive tasks. In this study, idiom comprehension was evaluated by means of a sentence-to-picture-matching task in 45 schizophrenic patients and 45 control subjects, matched for age and educational level. The task included 62 idiomatic and 62 literal sentences. Participants were presented with a written sentence, either literal or idiomatic, followed by a picture, which appeared below the sentence. They were instructed to judge whether the picture represented the meaning of the sentence or not, and responded by pressing one of two response keys. Half of the items correctly represented the meaning, half did not. Reaction times and accuracy were measured. Schizophrenics were impaired in both types of idiomatic sentence. However, their performance was particularly poor in the case of ambiguous idioms. Wisconsin Card Sorting Test and Digit Sequencing were the unique predictors of performance for idiom comprehension in general, while thought disorganization was not. Cognitive decline either did not appear to predict performance.